Cathelicidin peptide LL-37: A multifunctional peptide involved in heart disease - Shuo Miao; Houde Liu; Qingyu Yang; Yaping Zhang; Tao Chen; Shuai Chen; Xin Mao; Qingsong Zhang (Pharmacological Research)
Heart disease is a common human disease with high morbidity and mortality. Timely and effective prevention and treatment is an urgent clinical problem. The pathogenesis of heart disease is complex and diverse, involving hypertension, diabetes, atherosclerosis, drug toxicity, thrombosis, infection and other aspects. LL-37, an endogenous peptide, is well known for its antimicrobial properties. In recent years, LL-37 has been found to have a variety of biological functions, including its role in the regulation of atherosclerosis, thrombosis, inflammatory responses, and cardiac hypertrophy. Engineered LL-37-related peptides were developed and proved to regulate the development of disease, which revealed its potential clinical application. A comprehensive review and summary of LL-37 is presented to clarify its role in heart disease and to provide a reference and direction for future research.